Sustainability and future food security—A global perspective for livestock production. (26th November 2018) - Michalk, David L.; Kemp, David R.; Badgery, Warwick B.; Wu, Jianping; Zhang, Yingjun; Thomassin, Paul J.
Abstract: Grasslands are the predominant forage source for grazing animals and cover more of the Earth's land than any other major vegetation type. Their values are not always recognised, and conversion to other uses is continuing at a high rate leading to greater environmental and socio‐economic problems. Overgrazing is one of the main drivers of productivity decline of grasslands, reflecting the pressures from excessive human populations and a demand for food. Some 20% of the world's grasslands are in a severely degraded state; others have suffered shifts to less‐desirable species. Biodiversity and greenhouse gas production have also been particular concerns. Estimates of productivity change all show a decline over recent decades, yet animal numbers continue to increase, particularly in the developing world. This paper critically reviews the projected demands for livestock products, driven largely by human population growth; the current health of the world's grasslands and how current livestock systems that depend on land conversion and overexploitation of grassland are inappropriate and need to be improved. Central to this argument is that small holders in the developing world will be responsible for a large amount of the future red meat production, and this can be achieved through more efficient livestock production systems using lower stocking rates. The Australian sheep industry is provided as an example of how livestock production and reduced environmental impacts can be achieved with improved efficiency. Changes will require smallholders to transition to a competitive, market‐oriented livestock industry, which will provide challenges.